Propuesta de un texto guía para la enseñanza aprendizaje en la asignatura de contabilidad para los estudiantes de bachillerato en la especialización de contabilidad y administración en el instituto superior LA MANÁ. - Moreira Quiroz, Wilson Manuel (2017)
The objective of this research generated was to design a text with the program content of the subject accounting degree training required to take account of new performance features for professional sceneries also have changed. Actually the specialty training in accounting is conducting an administrative arrangements treasury and accounting records in a particular institution's contribution becomes textbook support in the teaching-learning process of accounting to raise the level of student performance. In the process research methods as they were used: analysis in the presentation of survey results, the synthesis of the conclusions; in statistics in the presentation of the results of research and scientifically applied in preparing the final report. Accounting students should aim to have a profile of technical expertise in banking accountancy Institute "The Manna", bearing in mind that you should apply the knowledge acquired with pract